Crossmodal interactions in the perception of expressivity in musical performance. - Vuoskoski, J; Thompson, MR; Clarke, E; Spence, C (Psychonomic Society Inc., 2014)
In musical performance, bodily gestures play an important role in communicating expressive intentions to audiences. Although previous studies have demonstrated that visual information can have an effect on the perceived expressivity of musical performances, the investigation of audiovisual interactions has been held back by the technical difficulties associated with the generation of controlled, mismatching stimuli.With the present study, we aimed to address this issue by utilizing a novel method in order to generate controlled, balanced stimuli that comprised both matching and mismatching bimodal combinations of different expressive intentions. The aim of Experiment 1 was to investigate the relative contributions of auditory and visual kinematic cues in the perceived expressivity of piano performances, and in Experiment 2 we explored possible crossmodal interactions in the perception of auditory and visual expressivity. The results revealed that although both auditory and visual kinematic cues contribute significantly to the perception of overall expressivity, the effect of visual kinematic cues appears to be somewhat stronger. These results also provide preliminary evidence of crossmodal interactions in the perception of auditory and visual expressivity. In certain performance conditions, visual cues had an effect on the ratings of auditory expressivity, and auditory cues had a small effect on the ratings of visual expressivity.